INTERNAL CONTROL SYSTEM ANALYSIS ON ACCOUNTS RECEIVABLE IN SP CORPORATION - Nicholas Renaldo; Sudarno Sudarno; Marice Br. Hutahuruk (The Accounting Journal of Binaniaga, 2020)
This study aims to identify and determine the effectiveness of the internal control of accounts receivable at SP Corporation. The problems are there are outstanding accounts receivable and at the end of 2013-2019, that accounts receivable will be written off. The main model theory used in this research is COSO to detect internal control effectiveness. This research used descriptive analysis and sign test. The conclusion based on the results of the sign test calculation showed that internal control of accounts receivable in SP Corporation is not working effectively. SP Corporation has not implemented the control environment, risk assessment, control activity, and supervision and monitoring effectively.